Implementation of Christian Ethical Values for HKI Seisemayang Medan Special Resort Sunday School Children through the Cheerful Sunday Method by IAKN Tarutung Students - Sianturi, Desy Ruth; Rajagukguk, Desi; Christopel Tambunan; Bella Simanjuntak; Patar Nababan; Robinhot Sihombing (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the implementation of Christian ethical values ​​for HKI Seisemayang Special Resort Sunday school children through the Cheerful Sunday method which was carried out by 5 IAKN Tarutung students for 3 months. A qualitative approach was used by collecting data through participant observation, in-depth interviews, and analysis of related documents. The research results showed that after implementing Cheerful Sunday, togetherness and friendship between Sunday school children increased, they applied politeness and Christian ethics, and reduced the use of negative sentences. The children became enthusiastic about participating in the worship service and invited other friends. Through games that combine groups, teachers teach children to love each other, work together, and form true friendships in Christ. This method has proven effective in developing the spirituality and ethics of Sunday school children in a fun way.